Adherence to Mediterranean Diet and Risk of Cancer: An Updated Systematic Review and Meta-Analysis - Schwingshackl, Lukas; Schwedhelm, Carolina; Galbete, Cecilia; Hoffmann, Georg (Nutrients, 2017)
The aim of the present systematic review and meta-analysis was to gain further insight into the effects of adherence to Mediterranean Diet (MedD) on risk of overall cancer mortality, risk of different types of cancer, and cancer mortality and recurrence risk in cancer survivors. Literature search was performed using the electronic databases PubMed, and Scopus until 25 August 2017. We included randomized trials (RCTs), cohort (for specific tumors only incidence cases were used) studies, and case-control studies. Study-specific risk ratios, hazard ratios, and odds ratios (RR/HR/OR) were pooled using a random effects model. Observational studies (cohort and case-control studies), and intervention trials were meta-analyzed separately. The updated review process showed 27 studies that were not included in the previous meta-analysis (total number of studies evaluated: 83 studies). An overall population of 2,130,753 subjects was included in the present update. The highest adherence score to a MedD was inversely associated with a lower risk of cancer mortality (RRcohort: 0.86, 95% CI 0.81 to 0.91, I2 = 82%; n = 14 studies), colorectal cancer (RRobservational: 0.82, 95% CI 0.75 to 0.88, I2 = 73%; n = 11 studies), breast cancer (RRRCT: 0.43, 95% CI 0.21 to 0.88, n = 1 study) (RRobservational: 0.92, 95% CI 0.87 to 0.96, I2 = 22%, n = 16 studies), gastric cancer (RRobservational: 0.72, 95% CI 0.60 to 0.86, I2 = 55%; n = 4 studies), liver cancer (RRobservational: 0.58, 95% CI 0.46 to 0.73, I2 = 0%; n = 2 studies), head and neck cancer (RRobservational: 0.49, 95% CI 0.37 to 0.66, I2 = 87%; n = 7 studies), and prostate cancer (RRobservational: 0.96, 95% CI 0.92 to 1.00, I2 = 0%; n = 6 studies). Among cancer survivors, the association between the adherence to the highest MedD category and risk of cancer mortality, and cancer recurrence was not statistically significant. Pooled analyses of individual components of the MedD revealed that the protective effects appear to be most attributable to fruits, vegetables, and whole grains. The updated meta-analysis confirms an important inverse association between adherence to a MedD and cancer mortality and risk of several cancer types, especially colorectal cancer. These observed beneficial effects are mainly driven by higher intakes of fruits, vegetables, and whole grains. Moreover, we were able to report for the first time a small decrease in breast cancer risk (6%) by pooling seven cohort studies.